Employee-Driven Innovation in Health Organizations: Insights From a Scoping Review - Stephanie B.M. Cadeddu; Labante Outcha Dare; Jean-Louis Denis (Kerman University of Medical Sciences, 2023)
Background  Employee-driven innovation (EDI) occurs when frontline actors in health organizations use their firsthand experience to spur new ideas to transform care. Despite its increasing prevalence in health organizations, the organizational conditions under which EDI is operationalized have received little scholarly attention.Methods  This scoping review identifies gaps and assembles existing knowledge on four questions: What is EDI in health organizations and which frontline actors are involved? What are the characteristics of the EDI process? What contextual factors enable or impede EDI? And what benefits does EDI bring to health organizations? We searched seven databases with keywords related to EDI in health organizations. After screening 1580 studies by title and abstract, we undertook full-text review of 453 articles, retaining 60 for analysis. We performed a descriptive and an inductive thematic analysis guided by the four questions.Results  Findings reveal an heterogeneous literature. Most articles are descriptive (n = 41). Few studies are conceptual and empirical (n = 15) and four are conference papers. EDI was often described as a participatory, learning innovation process involving frontline clinical and non-clinical staff and managers. Majority EDI were top-down, often driven by the organization's focus on participatory improvement and innovation and research-based initiatives. Five categories of methods is used in top-down EDI, two thirds of which includes a learning, a team and/or a digital component. Hybrid EDI often involves a team-based component. Bottom-up EDI emerged spontaneously from the work of frontline actors. Enablers, barriers, and benefits of EDI are seen at macro, organizational, team and individual levels; some benefits spread to other health organizations and health systems.Conclusion  This scoping review provides a comprehensive understanding of the organizational conditions under which EDI is operationalized. It offers insights for researchers, health organizations, and policy-makers about how and why frontline actors' involvement is crucial for the transformation of care.